Concept Mapping: Implementation in an EFl Classroom - Shaul, Melanie (Mediterranean Journal of Social Sciences, 2011)
This study looks at the impact of student-generated, concept mapping on the performance of EFL, grade 12, studentsin reading comprehension texts. In doing so, 14 EFL, grade 12, students were selected from a high school in Israel. Studentswere tested on three separate occasions. First, students were given a tutorial on how to create a visual aid, more specificallyconcept maps, during reading. Then students partook in three lessons; whereby, they employed concept mapping strategies.After each lesson, students completed reading comprehension tests based on the text that they had read. In addition followingeach tests, students were interviewed in order to assess their disposition towards self-generated, concept mapping. The resultsindicate that self-generated concept mapping by low-knowledge students had a significantly greater influence on students’ textcomprehension than did the self-generated concept mapping by high-knowledge students or both control groups. In addition,students' disposition toward self-generated concept mapping had a progressive positive change, regardless of students’ level.Concept mapping, EFL, self-generated